2017
DOI: 10.12659/msm.902261
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tibial Intramedullary Nailing Guided by Digital Technology Versus Conventional Method: A Prospective Study

Abstract: BackgroundThis prospective study aimed to compare clinical effects of intramedullary nailing guided by digital and conventional technologies in treatment of tibial fractures.Material/MethodsThirty-two patients (mean age 43 years, 18 males and 14 females) who were treated for tibial fractures from October 2010 to October 2012 were enrolled. They were sequentially randomized to receive intramedullary nailing guided by either digital technology (digital group, n=16) or conventional technology (conventional group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 27 publications
(21 reference statements)
0
10
0
1
Order By: Relevance
“…16 studies reported on operation time (Li et al, 2015(Li et al, , 2019Zhang et al, 2015;Liu et al, 2017;Chen et al, 2018Chen et al, , 2019Chen et al, , 2020Hung et al, 2019;Huang et al, 2020;Wang et al, 2020cWang et al, , 2020aBoudissa et al, 2021aBoudissa et al, , 2021bLong et al, 2021;He et al, 2022;Zheng et al, 2022). All studies, except for , found that using computer-assisted planning leads to a significantly shorter operation time compared to conventional planning.…”
Section: Operation Timementioning
confidence: 99%
See 3 more Smart Citations
“…16 studies reported on operation time (Li et al, 2015(Li et al, , 2019Zhang et al, 2015;Liu et al, 2017;Chen et al, 2018Chen et al, , 2019Chen et al, , 2020Hung et al, 2019;Huang et al, 2020;Wang et al, 2020cWang et al, , 2020aBoudissa et al, 2021aBoudissa et al, , 2021bLong et al, 2021;He et al, 2022;Zheng et al, 2022). All studies, except for , found that using computer-assisted planning leads to a significantly shorter operation time compared to conventional planning.…”
Section: Operation Timementioning
confidence: 99%
“…All studies that investigated fluoroscopy frequency (Liu et al, 2017;Chen et al, 2018Chen et al, , 2020Huang et al, 2020;Wang et al, 2020c;Long et al, 2021;He et al, 2022) found that using VSP leads to significantly less intra-operative fluoroscopies. The meta-analysis resulted in an overall standardized mean difference of -2.18 (95% CI: -2.75, -1.61), see Figure 4C.…”
Section: Fluoroscopy Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…У разі добре виконаного остеосинтезу та відповідного перебігу консолідації, причиною інвалідності у більшості випадків є нераціональний вибір тактики, або навіть повне нехтування реабілі-таційного лікування [4,6,8,9]. Ряд питань, пов'яза-них з так званою "остеогенною недостатністю", залишаються невирішеними [3,5,6,8,10].…”
Section: основні вектори медичної реабілітації в лікуванні діафізарниunclassified